2021
DOI: 10.1093/icb/icab196
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Glucocorticoid Plasticity Using Reaction Norm Approaches: There Still is So Much to Discover!

Abstract: Synopsis Hormones are highly responsive internal signals that help organisms adjust their phenotype to fluctuations in environmental and internal conditions. Our knowledge of the causes and consequences of variation in circulating hormone concentrations has improved greatly in the past. However, this knowledge often comes from population-level studies, which generally tend to make the flawed assumption that all individuals respond in the same way to environmental changes. Here, we advocate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 88 publications
2
49
0
1
Order By: Relevance
“…In addition, by adopting a reaction norm approach to modelling stress physiology, as recently advocated by ourselves ( Houslay et al, 2019 ) and others (e.g. Fürtbauer et al, 2015 ; Hau and Goymann, 2015 ; Taff and Vitousek, 2016 ; Guindre-Parker, 2020 ; Malkoc et al, 2021 ), we detect GxE reflecting genetic differences in the extent of habituation to the stressor over repeated exposures. This result is potentially important because poor habituation of the hypothalamic-pituitary-adrenal/interrenal (HPA/I) response to repeated or ongoing stressors can lead to well documented health problems in human and animal populations ( Segerstrom and Miller, 2004 ; Koolhaas, 2008 ; Romero et al, 2009 ; Mason, 2010 ).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, by adopting a reaction norm approach to modelling stress physiology, as recently advocated by ourselves ( Houslay et al, 2019 ) and others (e.g. Fürtbauer et al, 2015 ; Hau and Goymann, 2015 ; Taff and Vitousek, 2016 ; Guindre-Parker, 2020 ; Malkoc et al, 2021 ), we detect GxE reflecting genetic differences in the extent of habituation to the stressor over repeated exposures. This result is potentially important because poor habituation of the hypothalamic-pituitary-adrenal/interrenal (HPA/I) response to repeated or ongoing stressors can lead to well documented health problems in human and animal populations ( Segerstrom and Miller, 2004 ; Koolhaas, 2008 ; Romero et al, 2009 ; Mason, 2010 ).…”
Section: Discussionmentioning
confidence: 79%
“…Thus, it is likely that both mechanistic and evolutionary forces play a role in the causes of variation in endocrine flexibility. Recent reviews have addressed the environmental conditions that might favor endocrine flexibility and some mechanisms that could contribute to variation in endocrine flexibility (Guindre-Parker, 2020; Hau et al, 2016;Malkoc et al, 2021;Taff and Vitousek, 2016;Wada and Sewall, 2014).…”
Section: Investigating the Causes Of Variation In Endocrine Flexibili...mentioning
confidence: 99%
“…Individuals may also exhibit endocrine flexibility in either their baseline or induced hormone levels across environmental contexts (Guindre-Parker, 2020). Endocrine flexibility might be quantified by calculating endocrine scope and speed or by using reaction norms (see Glossary; Guindre-Parker, 2020; Malkoc et al, 2021). Using the reaction norm approach, endocrine flexibility is derived from the intercept and slope of hormone concentrations measured across contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals can differ in how strongly they respond to variation in ambient temperature, for instance in metabolic rate (Briga & Verhulst, 2017;Careau et al, 2014;Kar et al, 2021), foraging activity (Hall & Chalfoun, 2019), or incubation behavior (Cones et al, 2021). Since glucocorticoids support the regulation of such traits (Romero & Wingfield, 2016), quantifying the extent of glucocorticoid plasticity within and among individuals of wild vertebrate populations is crucial for evaluating the potential of these mechanisms to evolve (e.g., Angelier & Wingfield, 2013;Guindre-Parker, 2020;Hau et al, 2016;Malkoc, Mentesana, et al, 2021;Taff & Vitousek, 2016;Wada & Sewall, 2014). Individual differences are the raw material of selection, and for evolution to occur these individual differences have to harbor a heritable component.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggested that individual differences in glucocorticoid reaction norm elevations and slopes exist in wild vertebrate populations (summaries: Guindre-Parker, 2020; Malkoc, Mentesana, et al, 2021;Taff & Vitousek, 2016). However, some of these studies determined glucocorticoid metabolites from excrements (feces: Guindre-Parker et al, 2019;urine: Sonnweber et al, 2018), which can be additionally influenced by individual differences in dietary, metabolic, digestive and other processes (reviews in: Dantzer et al, 2014;Gormally & Romero, 2020;Goymann, 2012).…”
Section: Introductionmentioning
confidence: 99%